Modeling and stability analysis of interaction between converters in AC-DC distribution systems - Chen, Tao; Feng, Depin; Wu, Xiaobin; Lu, Changlu; Xu, Bing (Frontiers in Energy Research, 2023)
With the development and promotion of AC-DC distribution systems, the stability of multi-terminal systems has drawn much interest. This paper analyzes the instability phenomena in AC-DC distribution systems by considering the interactions between converters. The typical structure and control strategy of double-terminal AC-DC distribution systems under master-slave control is introduced. Then an AC-DC distribution system model is developed taking into account the interaction of the converter control system. The resonant spikes generated by the interaction between the converters are used as the reference object of the interaction to analyze the influence of the converter control parameters and the system electrical parameters on the system stability and interaction. Finally, a double-terminal AC/DC distribution system model is built using PLECS and RTBOX for simulation and semi-physical experimental verification.